Characteristics of lactobacillus plantarum LIP-1 microcapsules prepared using an aqueous phase separation method. (July 2020) - Ma, Lili; Huo, Qiwen; Zhang, Qiaoling; E, Jingjing; Zhao, Lihua; Wang, Junguo
Abstract: The emulsification method (EM) is popular for microencapsulating probiotics with lactoprotein as the wall material. We have developed an aqueous phase separation method (APSM) based on this technique by replacing emulsification with fermentation. Compared with the EM microcapsules, the electrophoresis results showed that the wall materials of the microcapsules prepared using the APSM consisted of more protein fragments after fermentation. Plate-counting results revealed porliferation of the core material — Lactobacillus plantarum LIP-1 ). Microencapsulation efficiency of the APSM microcapsules of 82 ± 5%, particle size of 80 ± 5 μm, survival rate in simulated gastric fluid of 85 ± 5%, survival rate after freeze-drying of 88.4%, and prolonged shelf-life. These characteristics were all significantly better than those of the EM microcapsules ( P  < 0.05). Scanning electron microscopy showed that the surface structure of the APSM microcapsules was more compact, which helped improve the resistance of the probiotics to adverse environments. The APSM overcame the disadvantages of the EM and produced microcapsules with superior characteristics; thus, it has broad prospects in industrial development. Highlights: A novel microencapsulation method was developed by fermentation. There are beneficial interactions between core material and wall matrices. Reduce cost of oil and some undesirable reactions of oil.